Relationship Between Arm Muscle Endurance and Hand Eye Alignment with Lower Passing Proficiency of Male Volleyball Extracurricular Participants of SMAN 1 Karangdowo Klaten - Raharja, Muhammad Miftahul Fadhil; Abdulaziz, Moch Fahmi (UNIVERSITAS NEGERI MAKASSAR, 2025)
The purpose of this study was to evaluate the relationship between arm muscle stamina and visual-motor alignment with lower passing skills for male members of extra volleyball activities at SMAN 1 Karangdowo, Klaten. This study utilized a survey method using a correlational quantitative approach. The research subjects involved 20 male students who actively participated in volleyball extracurricular training. Measurements were taken using three instruments: first, the push and pull dynamometer test to assess arm muscle strength; second, the hand-eye coordination test was conducted through throwing and catching tennis balls; and third, the Brumbach Forearms Pass Wall-Volley test was used to calculate lower passing skills. The findings of this study showed a significant correlation between the two physical variables and students' lower passing performance.